2012
DOI: 10.1007/s10484-012-9186-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Awakening Response and Pain-Related Fear-Avoidance Versus Endurance in Patients Six Months After Lumbar Disc Surgery

Abstract: Recent research indicates that stress-induced, prolonged deviations in basal adrenocortical activity might contribute to ongoing/recurrent pain following lumbar disc surgery. Further, fear-avoidance and endurance responses to pain (FAR and ER) are regarded as important risk factors for pain after surgery. In patients with non-specific low back pain, FAR appear to possibly increase pain-related arousal, whereas ER may have an arousal-lowering effect, indicated by adrenocortical activity. The current study explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Moreover, persisting pain after surgery may be due to an association between psychological factors and pain that was already existent before surgery. Therefore, various authors suggested to introduce psychological screenings to identify patients at risk for pain chronification [15,36,38,39,42,48] and expand preventative approaches [55], as well as psychological interventions, in addition to routine surgical treatment [21,22,38,39,42,48]. A strong association between coping behavior and depressive symptoms was found by three independent studies [39,41,48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, persisting pain after surgery may be due to an association between psychological factors and pain that was already existent before surgery. Therefore, various authors suggested to introduce psychological screenings to identify patients at risk for pain chronification [15,36,38,39,42,48] and expand preventative approaches [55], as well as psychological interventions, in addition to routine surgical treatment [21,22,38,39,42,48]. A strong association between coping behavior and depressive symptoms was found by three independent studies [39,41,48].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various kinds of substances indicating a physiological stress response, the s-IgA and α-amylase activity in the saliva have been used in many studies as useful indicators of physiological stress because they can be easily collected and impose little burden on subjects [13,[15][16][17]23,29]. The s-IgA in saliva is an indicator of the level of activity of the sympathetic nervous system, parasympathetic nervous system and immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Different from blood, collection of saliva to investigate physiological stress can be performed non-invasively, without causing pain or burden to the subjects and by non-medical people; hence, many studies have been performed using saliva [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…After lumbar discectomy, patients express little understanding of the surgical procedure, confusion regarding activity limitations and develop a fear of movement and reinjury 41. Elevated fear-avoidance responses following lumbar disc surgery are associated with higher pain-related stress42 and worse clinical outcomes 43. It has been suggested that high-intensity postdiscectomy exercise programmes allow patients to confront their fears and insecurities and that this process may in part explain the effect of postoperative exercise programmes 44.…”
Section: Discussionmentioning
confidence: 99%